Synergizing the academic credit bank system and the Thai national digital learning massive open online course platform for lifelong learning: A data-mining approach - Thammetar, Thapanee; Khlaisang, Jintavee; Theeraroungchaisri, Anuchai (Humanities, Arts and Social Sciences Studies, 2025)
This study analyzes user behavior to support the development of Thai massive open online course (MOOC) in Thailand. Data analysis was conducted using data-mining techniques on questionnaire responses from 2,230 users. The study obtained the following results. Analysis of learners’ basic information and course trends derived from MOOC courses reveal that more than 250 students design a micro credit and alternative credit system, including a credit bank system. In terms of user interface, the results underscore the formats of contents, activities, and learning styles. Lastly, analysis of basic data on the Thai MOOC digital learning platform indicates that further development of the academic credit bank system is required. The study identified the need for a curriculum that focuses on vocational skills to develop work competencies, the accumulation and transfer of credits between universities, and recognition of previous credits and certificates to pursue a master’s degree. Thai MOOC users were mainly composed of students (30.04%), government officials (25.65%), and private employees (14.44%). In general, learners sought to upskill (83.41%), apply learning to daily life (68.57%), and conduct interest-based study (68.21%). We observed two patterns of registration in three consecutive courses, namely, (1) Personality, Psychology, and Adjustment; Startup: Pushing your Dream; and Consumer Behavior and Retailing Business in the Digital Age and (2) Startup: Pushing your Dream; Online Store Entrepreneur; and Consumer Behavior and Retail Business in the Digital Era. The top three patterns of registration in two consecutive courses included: (1) English for Communication and English Start Up, (2) English for Communication and Easy English for Everyday Life, and (3) Psychology and Daily Life and English for Communication.